A transparent distributed ledger-based certificate revocation scheme for VANETs. (March 2023) - Tesei, Andrea; Lattuca, Domenico; Luise, Marco; Pagano, Paolo; Ferreira, Joaquim; Bartolomeu, Paulo C.
Abstract: The widespread adoption of Cooperative, Connected, and Automated Mobility (CCAM) applications requires the implementation of stringent security mechanisms to minimize the surface of cyber attacks. Authentication is an effective process for validating user identity in vehicular networks. However, authentication alone is not enough to prevent dangerous attack situations. Existing security mechanisms are not able to promptly revoke the credentials of misbehaving vehicles, thus tolerate malicious actors to remain trusted in the system for a long time. The resulting vulnerability window allows the implementation of complex attacks, thus posing a substantial impairment to the security of the vehicular ecosystem. In this paper we propose a Distributed Ledger-based Vehicular Revocation Scheme that improves the state of the art by providing a vulnerability window lower than 1 s, reducing well-behaved vehicles exposure to sophisticated and potentially dangerous attacks. The proposed scheme harnesses the advantages of the underlying Distributed Ledger Technology (DLT) to implement a privacy-aware revocation process while being fully transparent to all participating entities. Furthermore, it meets the critical message processing times defined by EU and US standards, thus closing a critical gap in the current international standards. Theoretical analysis and experimental validation demonstrate the effectiveness and efficiency of the proposed scheme, where DLT streamlines the revocation operation overhead and delivers an economically viable yet scalable solution against cyber attacks on vehicular systems.